2000
DOI: 10.1093/ndt/15.9.1367
|View full text |Cite
|
Sign up to set email alerts
|

Immunoadsorption onto protein A induces remission in severe systemic lupus erythematosus

Abstract: Immunoadsorption onto protein A might be used as an extracorporeal treatment option in SLE when other therapies are ineffective.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
61
0
2

Year Published

2004
2004
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(63 citation statements)
references
References 20 publications
0
61
0
2
Order By: Relevance
“…In particular, plasma exchange is not effective in the treatment of SLE [7]. However, immunoadsorption using protein A, C1q, or dextran sulfate cellulose columns has been shown to be useful for refractory SLE [8,9]. A recent open-label study of 16 patients with LN who were either refractory or intolerant to cyclophosphamide (CY) showed that vigorous removal of IgG by immunoadsorption was beneficial in most patients, with amelioration of proteinuria and global disease activity scores [10].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In particular, plasma exchange is not effective in the treatment of SLE [7]. However, immunoadsorption using protein A, C1q, or dextran sulfate cellulose columns has been shown to be useful for refractory SLE [8,9]. A recent open-label study of 16 patients with LN who were either refractory or intolerant to cyclophosphamide (CY) showed that vigorous removal of IgG by immunoadsorption was beneficial in most patients, with amelioration of proteinuria and global disease activity scores [10].…”
Section: Discussionmentioning
confidence: 99%
“…The majority of the reports of lupus podocytopathy suggest that T cell activation plays an important role in the pathogenesis by altering the production of cytokines and circulating glomerular toxins, as proposed in idiopathic minimal change glomerulopathy [3,[17][18][19]. Since circulating autoantibodies and immune complexes may contribute significantly to the pathogenesis of SLE, an extracorporeal method for the removal of these pathological antibodies and complexes could be effective in the treatment of active LN [8]. The purpose of DFPP treatment is removal of pathologic hypermolecules, including cytokines and circulating glomerular toxins, in addition to the circulating autoantibodies and immune complexes in our case.…”
Section: Discussionmentioning
confidence: 99%
“…Immunoadsorption using a C1q column to bind immune complexes, C-reactive protein, DNA, and other activators of the immune system has been used on eight adults [29] with some encouraging results. In addition, a staphylococcal protein A column has been used to remove antibodies and immune complexes in another report [30]. Both treatments were targeted at those with severe therapy-resistant SLE.…”
Section: Discussionmentioning
confidence: 99%
“…Braun et al examined eight patients (six with LN class III or IV) with severe SLE resistant to conventional treatment who underwent extracorporeal immunoadsorption onto staphylococcal protein A (58). Most of the patients demonstrated a reduction in levels of anti-dsDNA antibody and circulating immune complexes, as well as improvement of disease activity and renal function with a reduction in serum creatinine levels and degree of proteinuria.…”
Section: Plasmapheresis and Immunoadsorptionmentioning
confidence: 99%